(untitled) (JISIP (Jurnal Ilmu Sosial dan Pendidikan), 2022)
Online learning in addition to providing many conveniences, there are also obstacles, giving rise to various student perceptions. The purpose of this study was to describe students’ perceptions of online learning in the Electrical Lighting Installation (IPL) training courses at SMKN 2 Bima City. This research method uses qualitative research. The informants in this study were students of class XII Electrical Power Instillation Engineering SMKN 2 Bima City, totaling 32 students and IPL teachers at SMKN 2 Bima City, namely Mr. Gufran, S.Pd. Data collection techniques used in this study were interviews through the google form application, and documentation. The analysis technique uses qualitative techniques. The results of the study revealed that the majority of students had negative perceptions of online learning of IPL subject matter. This is because the majority of students do not understand the online learning material that is delivered, the method of delivering IPL material is considered less attractive and students’ opinions about online learning are considered less effective. The obstacles faced during online learning are internet quotas, a weak signal to access materials during online learning, and students’ understanding of the material presented by the teacher is not optimally accepted. The solution to overcome the problems of online learning is: for teachers, so that they can learn and share with other teachers, not only in one school but in other schools so that teaching can vary. For students, they are more active and more enthusiastic, and can look for other learning references, and for schools, it is better to have new programs during a pandemic like this, for example: conducting training that is attended by teachers and providing a computer laboratory room for making learning videos.